The Influence of Observational Learning on Consumer Purchase Intention is Mediated by Perceived Message Authenticity and Consumer Attitudes - Putra, Annafa Nandhira; Soepatini, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: The purpose of this research is to test the hypothesis that has been established by testing the relationship between variables using a numerical approach, namely to find out how observational learning influences purchase intentions through perceptions of message authenticity and consumer attitudes. Methodology: The Hair formula was used to calculate the number of samples so that 132 respondents were obtained. Data was obtained directly from filling out online questionnaires from respondents who met the research sample criteria. Data analysis was carried out using Structural Equation Modeling (SEM) using the Partial Least Square (PLS) model evaluation with the SmartPLS 3 software application program. Results: The research results showed the positive influence of observational learning on consumer attitudes and perceived message authenticity. Furthermore, it shows a positive correlation between observational learning and purchase intention. The research results also show a good correlation between perceived message authenticity and consumer attitudes towards purchase intentions. Applications/Originality/Value: By using influencers' roles, businesses can better shape consumers' purchase intentions. This demonstrates the clear relationship between observational learning and customer purchase intentions. Employing influencers with skill in product promotion will strengthen the bond between the influencer and the product, increasing the likelihood that customers will make a purchase.